2001
DOI: 10.1021/jp010022n
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Dynamic Properties of the Peridinin Lowest Singlet Excited States

Abstract: Spectroscopic properties as well as excited state dynamics of the carotenoid peridinin in several solvents of different polarities were investigated by time-resolved fluorescence and transient absorption techniques. A strong dependence of the peridinin lowest excited states dynamics on solvent polarity was observed after excitation into the strongly allowed S 2 state. Peridinin relaxes to the ground state within 10 ps in the strongly polar solvent methanol, while in the nonpolar solvent n-hexane a 160 ps lifet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
342
2
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(376 citation statements)
references
References 35 publications
25
342
2
7
Order By: Relevance
“…It can be speculated that the cyclopentanone ring is involved in this localization step. This assumption is likely because other groups having observed a decay pattern very similar to the one reported here, made their observations in peridinin, a carotenoid highly substituted and possessing a cyclopentanone ring as well [99][100][101][102]. This assumption is further corroborated by experimental results obtained on magnesium octaethylporphyrin (MgOEP) (data not shown) as MgOEP, in contrast to the structurally similar PChla, which in addition has an attached cyclopentanone ring to the porphyrin macrocycle, does not exhibit any significant excited-state dynamics, when directly being promoted into the Q 00 band [22].…”
Section: Protochlorophyllide Asupporting
confidence: 82%
See 2 more Smart Citations
“…It can be speculated that the cyclopentanone ring is involved in this localization step. This assumption is likely because other groups having observed a decay pattern very similar to the one reported here, made their observations in peridinin, a carotenoid highly substituted and possessing a cyclopentanone ring as well [99][100][101][102]. This assumption is further corroborated by experimental results obtained on magnesium octaethylporphyrin (MgOEP) (data not shown) as MgOEP, in contrast to the structurally similar PChla, which in addition has an attached cyclopentanone ring to the porphyrin macrocycle, does not exhibit any significant excited-state dynamics, when directly being promoted into the Q 00 band [22].…”
Section: Protochlorophyllide Asupporting
confidence: 82%
“…They show that in n-hexane the barrier is high enough to prevent the population of the S ICT state to take place and only the S 1 → S 0 internal conversion is observed. These authors report on a decreasing barrier in parallel with increasing solvent polarity resulting in a quenching of the S 1 state by means of the S 1 → S ICT relaxation [99]. The results obtained in the course of this work might be explained in analogy to the arguments given above; in the polar solvents acetonitrile and methanol the intramolecular charge-transfer state lies below the initially photopopulated S 1 state and is therefore accessible for population.…”
Section: Protochlorophyllide Asupporting
confidence: 68%
See 1 more Smart Citation
“…It was also recently shown that the lowest excited state of peridinin exhibits rather unusual behavior, in that its lifetime strongly depends on solvent polarity, the lifetime decreasing with an increase of the medium polarity. Polarity dependence was attributed to an intramolecular charge transfer (ICT) state in the excited state manifold of peridinin (16,17). Dynamics of the peridinin ICT state in polar solvent were recently studied by near-infrared femtosecond spectroscopy where it was shown that the ICT state can be detected via its pronounced stimulated emission band at Ϸ950 nm (17).…”
mentioning
confidence: 99%
“…4,19,[25][26][27][28][29][30][31][32][33] Previous investigations of DCM 19,23,34 considered the formation of a TICT state involving rotation about the C-N bond linking the dimethylamino group to the aromatic ring, or rotation of the dimethylaminobenzyl moiety, but these experiments lacked any direct probe of structural change. Another proposed state is one analogous to the P* state 26,30,35 of stilbenes in which the molecule adopts a perpendicular conformation about the central double bond as an intermediate between cis and trans configurations. Electronic structure calculations for DCM using CS INDO have been able to locate a singlet state with a dipole moment large enough match the experiment, and in this state DCM adopts a configuration in which the dimethylamino moiety is perpendicular to the aromatic ring.…”
Section: -16mentioning
confidence: 99%